Отражение радоновых аномалий в магнитном поле и тектонических элементах Беларуси - Гарецкий, Р.Г.; Каратаев, Г.И.; Матвеев, А.В. (Геофизический журнал, 2016)
Regularities connecting radon anomalies in soil air of cover deposits of different genesis with magnetic anomalies and tectonic elements of Belarus have been indirectly determined through genetic types of Quaternary deposits. It is noted that the intensity of radon anomalies increases with transition to the tectonic structures subjected to multi-step processes of activation. Linearly stretched radon anomalies correlate with the deep faults of lithosphere.